2016
DOI: 10.1134/s0040579516040448
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the drying of loosely-packed and heterogeneous municipal solid waste

Abstract: In this paper, experimental investigation on convective drying of mixed municipal solid wastes was conducted. The aim of this study was to determine the effect of temperature, change in composition and par ticle size on the overall drying rate coefficient and mass transfer coefficient. Particle size of the samples was determined and mass losses recorded with time when the samples were dried using convective dryer. Mass losses were used to determine moisture content, drying rate coefficient and mass transfer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Simulated materials used in this experiment consisted of plant wastes (from the university's dining hall), paper and plastic shreds, and wood chips and soil, which were thoroughly mixed in accordance with the proportions shown in Table 1. Three sets of simulated mixtures, which were based on data presented by different authors (Diaz et al, 2005;Nzioka et al, 2016;Rotich et al, 2006), were considered to represent the overall scenario of mixed MSW in the majority of the countries with developing and (to some extent) emerging economies. One of the limitations of this experiment was that the simulated mixtures were made with the aforementioned components on an 'as received' basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulated materials used in this experiment consisted of plant wastes (from the university's dining hall), paper and plastic shreds, and wood chips and soil, which were thoroughly mixed in accordance with the proportions shown in Table 1. Three sets of simulated mixtures, which were based on data presented by different authors (Diaz et al, 2005;Nzioka et al, 2016;Rotich et al, 2006), were considered to represent the overall scenario of mixed MSW in the majority of the countries with developing and (to some extent) emerging economies. One of the limitations of this experiment was that the simulated mixtures were made with the aforementioned components on an 'as received' basis.…”
Section: Methodsmentioning
confidence: 99%
“…Since the mixed MSW (i.e. simulated MSW) in question was considered to be loose/fluffy, particle size was determined using the formulas proposed by the following authors (Keey, 1992;Nzioka et al, 2016). The experimental analysis workflow is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, we used combustible materials and excluded all possible inert materials (glass, soil, metals etc.) We prepared two sets of samples as shown in Table 1 based on other references [5], [10], [11]. The particle size of sample MSW was <20 mm recommended by Athanaopolous [12], and reference [13]providedmathematical formulation for determining theparticle size of our sample MSW.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, various dryers such as bio-drying equipment, solar dryer, green house dryer and thermal dryers are being used for the pretreatment of biodegradable wastes to improve the waste quality. Most studies [35][36][37][38][39][40][41][42] evaluated the waste quality by different drying methods and studied a relationship between moisture reduction and heating value increases of solid wastes. In this paper, the study evaluated the quality of the biodegradable wastes of Yangon city by drying and highlighted a relationship between moisture reduction and weight reduction, moisture reduction and volume reduction, and moisture reduction and heating value increase of the biodegradable wastes of Yangon city.…”
Section: Background Of the Studymentioning
confidence: 99%
“…It was observed that the drying rates could vary depending on the amount and thickness of the waste samples. Therefore, by using a convective drying oven (Han Baek HB-502L) at the drying temperature of 100°C, Nzioka et al [45] gained approximately 40% of moisture reduction of 100-gram mixed waste sample in 30 minutes. In addition to the weight of the samples, the sizes and thickness of the samples, air flow rates, air flow directions, drying temperature, turning effects of waste samples and bulking agents would also affect the drying rates [33,37,40,42,46].…”
Section: (C) Statistical Analysismentioning
confidence: 99%